The Use of Sociodrama to Improve Class XI Bahasa Students' Active Participation and Speaking Achievement at Madrasah Aliyah Negeri 1 Jember in the 2016/ 2017 Academic Year - Moh. Fauzan; Zakiyah Tasnim; Sugeng Ariyanto (Pendidikan Fisika FKIP UNEJ, 2017)
Abstract: This research was classroom action research. The aim of this research was to improve class XI Bahasa students' active participation and speaking achievement at Madrasah Aliyah Negeri 1 Jember. The subject of the research was class XI Bahasa students of Madrasah Aliyah Negeri 1 Jember, the total number of the subject was 36 students. The data collection methods in this research used test, observation, interview, and documentation. Then, the obtained data (students' active participation and speaking achievement) from each cycle was analyzed quantitatively. The result of observation Cycle 1 showed that the average percentage was 78.84%. This result achieved the minimum requirement of the students' active participation (75%). The speaking test results Cycle 1 showed 77.8% students could achieve score of passing grade that was 75. Then, Cycle 2 was still conducted to check the consistency of the results in Cycle 1. The result of observation Cycle 2 showed that the average percentage was 88.56%. This result also achieved the minimum requirement of the students' active participation (75%). The speaking test results Cycle 2 showed 85.29% students also could achieve score of passing grade that was 75. It can be concluded that the Use of Sociodrama Improved Class XI Bahasa students' active participation and speaking achievement at Madrasah Aliyah Negeri 1 Jember in the 2016/ 2017 Academic Year. Keywords: Sociodrama, Speaking, Speaking Achievement